Pengaruh Penerapan Cadangan Kerugian Penurunan Nilai (CKPN) PSAK 239 (PSAK 55) dan Cadangan Kerugian Penurunan Nilai (CKPN) PSAK 109 (PSAK 71) Terhadap Kualitas Laba - Rahmi, Aulia; Yadiati, Winwin (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Banking institutions play a crucial role in supporting a country's economy, especially as a liaison between owners of surplus funds and parties who need funds through credit. Changes in financial accounting standards, which initially used PSAK 239 (PSAK 55) to become PSAK 109 (PSAK 71), regulate the recognition and measurement of financial instruments. PSAK 109 (PSAK 71) emphasizes the expected loss approach (forward-looking) compared to previous methods which are backward-looking. This implementation is expected to improve profit quality through more accurate calculation of Allowance for Impairment Losses, but it also has an impact on increasing CKPN which will affect the Company's profits. This research aims to understand the influence that CKPN PSAK 239 (PSAK 55) and CKPN PSAK 109 (PSAK 71) have on earnings quality as well as a comparative analysis. This research applies quantitative methods with a descriptive-comparative approach and simple linear regression data analysis techniques. The sample in this study was selected using techniques of purposive sampling. The subject of this research is banking listing on Bursa Efek Indonesia (BEI). The findings resulting from this research are that PSAK 239 (PSAK 55) and PSAK 109 (PSAK 71) both have a significant influence on earnings quality and there is a significant difference between earnings quality applied to PSAK 239 (PSAK 55) and PSAK 109 (PSAK 71).